Diagnostico financiero a la Cooperativa de Ahorro y Crédito San Antonio Ltda. del Cantón Montalvo en el periodo 2021- 2022. - Punina Cambo, Sandra Elizabeth (2024)
The present case study consists of analyzing the financial situation of the San Antonio Savings and Credit Cooperative Ltda, of the Montalvo canton during the period 2021-2022, for which the calculation of the financial ratios will be carried out, as well as the preparation of the horizontal analysis that allows us to compare the financial information of the cooperative over time to demonstrate the trends or changes that it has had in the aforementioned periods. In this case study, the need to know the financial situation and evolution of the cooperative is justified, for which it is also necessary to compare the ranking in the years 2021-2022, and verify how these have been increasing according to their income. of assets, since they are currently in segmentation 2. For the development, the analytical, inductive method and the transversal type of documentary research were used since it consists of the analysis of financial information from one year to the next. The conclusion shows the importance of applying financial ratios to evaluate the financial health of the entity, which allows administrative staff as well as partners and investors to make decisions.